2009
DOI: 10.2183/pjab.85.500
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cadmium induced crystal defects in developing rat tooth enamel

Abstract: It is well known that exposure to environmental cadmium causes itai-itai (ouch-ouch) disease. However, the exact mechanism underlying this bone disease remains unresolved. By focusing on the calcification mechanism, we examined developing tooth enamel in rats exposed to cadmium to test the hypothesis that cadmium exposure may cause defects in crystal formation. Electron microscopy revealed the presence of perforated crystals in developing tooth enamel, indicating that the process of crystal nucleation may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…This might be fatal to cellular metabolism and eventually lead to pathological calcification, which might be similar to the vascular calcification accompanying cellular degeneration [43]. On the other hand, the increase of osteoid caused by the relatively low dose of F treatment may be interpreted as an increase of amorphous minerals due to the failure of crystal nucleation observed in the present and the previous studies [13,14,43].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This might be fatal to cellular metabolism and eventually lead to pathological calcification, which might be similar to the vascular calcification accompanying cellular degeneration [43]. On the other hand, the increase of osteoid caused by the relatively low dose of F treatment may be interpreted as an increase of amorphous minerals due to the failure of crystal nucleation observed in the present and the previous studies [13,14,43].…”
Section: Discussionmentioning
confidence: 49%
“…The scientific justification for F therapy for osteoporosis, which induced irregular periosteal bone formation, ligament calcification, abnormal mineralization, and an increase of osteoid formation [29][30][31][32][33][34][35][36], is as follows: Concerning the high dose of F treatment, the increase of bone mineral density might be attributed to the pathological mineralization seen by an abnormal calcification and the presence of large crystals located outside the collagen fibrils [16,17,35,37]. This occurs because a high content of F ions absolutely inhibits the synthesis or activity of certain enzymes such as enolase and carbonic anhydrase [13,14,[38][39][40][41][42]. This might be fatal to cellular metabolism and eventually lead to pathological calcification, which might be similar to the vascular calcification accompanying cellular degeneration [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical analyses revealed that the catalytic activity of carbonic anhydrase in the immature enamel matrix declined remarkably [23]. The poor catalytic activity of cadmium-binding carbonic anhydrase might hinder the nucleation process, leading to impairment in mineralization [23]. The dental defects and its possible mechanism in Bhopal gas tragedy affected individuals and their preceding generations should be evaluated on a larger scale .The present study conducted had limitations that the findings were solely dependent on the opinion given by the practitioners.…”
Section: Discussionmentioning
confidence: 84%
“…Also, increased levels of cadmium could affect the crystal formation in the enamel. Biochemical analyses revealed that the catalytic activity of carbonic anhydrase in the immature enamel matrix declined remarkably [23]. The poor catalytic activity of cadmium-binding carbonic anhydrase might hinder the nucleation process, leading to impairment in mineralization [23].…”
Section: Discussionmentioning
confidence: 99%